Public health explored: 50 stories to change the world - Ashton, John (Critical Publishing, 2021)
An understanding of public health has never been more important!There has been a growing interest in public health, driven by concerns for social justice and sustainability, but it is currently in the headlines as never before. The failure of governments to get to grips with the Covid-19 pandemic has demonstrated widespread ignorance of the basics of a public health approach to threats to health and well-being.Relevant to all interested individuals but particularly students and professionals within nursing, medicine, social work and public health, this book encourages critical debate and reflection to develop a deep understanding of the complexities of public health issues. It offers 50 powerful stories and sayings around public health that could just change the world! Accompanied by searching questions for discussion and case studies that provide context and link each aphorism to a key event or theme, important messages around public health are extracted and explored.